Pengaruh Profitabilitas, Likuiditas, Leverage, dan Ukuran Perusahaan Terhadap Financial Distress Pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Putri Nadia Stepani; Lucky Nugroho (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the effect of Profitability, Liquidity, Leverage, and Company Size on Financial Distress. The population in this study are Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sample in this study was 75 companies out of 87 companies that met the criteria so that the total sample used in this study was 225 observational data. The research design used was quantitative research and the sampling method used in this study was purposive sampling method. The data used in this research is secondary data. The data analysis method used in this study is logistic regression analysis using the IBM SPSS version 22 application program. The results of the analysis show that (1) profitability has an effect on financial distress, (2) liquidity has an effect on financial distress, (3) leverage has no significant effect on financial distress, and (4) company size has no effect on financial distress. The implication of this research is to provide additional knowledge and references for academics and researchers related to the factors that influence financial distress. In addition, this research can also provide information that can assist in decision-making for practitioners and stakeholders who focus on financial distress. The novelty in this study is related to the object and period of research, namely the factors that cause financial distress in non-cyclical consumer companies in the 2019-2021 period.